Gestão dos resíduos sólidos urbanos: O Brasil e Portugal em perspectiva - Celeri, Marcio José; Cortez, Ana Tereza Cáceres [UNESP] (My University, 2017)
Portugal and Brazil started the first organized actions in the management of MSW (Municipal Solid Waste) in the 80s of the twentieth century. But it was only in the 90 Portugal rationalized that an integrated management of MSW and Brazil created several actions that can not always hang together. This article aims to present the evolution of management of municipal solid waste in Portugal and Brazil, to expose the difficulties and inconsistencies and challenges of their models. The methodology was based on literature research, descriptive and quantitative data available, interviews with relevant actors in the field. As a result we show that the successful implementation of a waste management system depends not only of economics, but it requires planning environmental and social principles as well as political will and commitment from key stakeholders, interests and stakeholders.
Management of solid urban waste: Brazil and Portugal in perspective
Keywords: Brazil; Portugal; Public policies; Urban solid waste management